Experimental and theoretical study on a novel multi-dimensional vibration isolation and mitigation device for large-scale pipeline structure. (15th August 2019) - Xu, Zhao-Dong; Ge, Teng; Miao, Annan
Abstract: The pipeline structure is prone to multi-dimensional vibration under the effect of external excitation, fluid pulsation and water hammer, which influences transportation efficiency and leads to accidents. In this paper, the multi-dimensional vibration isolation and mitigation device (MVIMD) is developed, which controls the vibration of the pipeline structure from two aspects simultaneously: isolating vibration and mitigating vibration. The device which consists of viscoelastic (VE) bearing, VE dampers and U-shaped springs, has energy dissipation capacities both in horizontal and vertical vibration due to employing VE material with high energy dissipation capacity. In order to investigate the mechanical properties of the device in the horizontal and vertical directions, the characterization tests under different frequencies and amplitudes are carried out. To accurately describe the nonlinear characteristics of the device caused by the complex viscoelasticity, the mathematical model for MVIMD is proposed for considering the effects of frequency and displacement amplitude based on the equivalent standard solid model. Finally, the numerical results are compared with the experimental data. It can be shown from comparison results that the proposed model can describe the properties of MVIMD precisely.